Transitividad. Produciendo rizoma en medio de Winnicott, Guattari y Deleuze (2013)
ABSTRACT: The purpose of this paper is to epistemologically articulate the clinics teachings of Donald Winnicott and philosophical thought of Felix Guattari and Gilles Deleuze. It specifically addresses the points of interception between the concept of the transitional and the machinic assemblage, based on the working hypothesis of a common reference to the transitive production of signs, that unfolds in the midst of one plane of immanence in which operate compositionally a multiplicity of elements for consistent training ofuncentered and mutable systems. For this exercise are used especially the article of english psychoanalyst «Transitional objects and transitional phenomenas» (1951/2008b), published in the posthumous edition of Playing and Reality (1971/2008a), and the text of french philosophers: «Rhizome», published in A Thousand Plateaus (1980/2006).